Conducting a desk review to inform the mental health and psychosocial support response to the 2016 Ecuador earthquake. Issue 4 (1st October 2016) - Troya, M. Isabela; Greene, M. Claire; Santos, Clara Gesteira; Shultz, James M.
ABSTRACT: Following the 7.8 magnitude earthquake that struck Ecuador on 16 April 2016, multiple salient public health concerns were raised, including the need to provide mental health and psychosocial support for individual survivors and their communities. The World Health Organization and the United Nations High Commissioner for Refugees recommend conducting a desk review to summarize existing information, specific to the affected communities, that will support timely, culturally-attuned assessment and delivery of mental health and psychosocial support shortly after the onset of a disaster or humanitarian emergency. The desk review is one component of a comprehensive toolkit designed to inform and support humanitarian actors and their responders in the field. This commentary provides a case example of the development of a desk review that was used to inform personnel responding to the 2016 earthquake in Ecuador. The desk review process is described in addition to several innovations that were introduced to the process during this iteration. Strengths and limitations are discussed, as well as lessons learned and recommendations for future applications.